Assessment of the Level of Economic Security in the Conditions of Uncertainty - Orlova, Anna V.; Lyshchikova, Julia V.; Nikulina, Yevgenia V.; Anokhin, Yevgeny I. (International Journal of Economics and Financial Issues, 2016)
The article is devoted to assessing the economic security of the state, projecting the resulting efficiency factor of socio-economic development in general. Assessment of economic security is presented as a set of socio-economic development indicators based on those parameters that reflect the impact of uncertainty on the conditions of economy security of the state. The values of economy security indicators of the Russian Federation are calculated for the period 2009-2014. Keywords: economic security, assessment of economic security, conditions of uncertainty JEL Classifcations: D8, F63, O1